Advanced Electrolytes for Fast‐Charging High‐Voltage Lithium‐Ion Batteries in Wide‐Temperature Range. Issue 22 (20th April 2020) - Zhang, Xianhui; Zou, Lianfeng; Xu, Yaobin; Cao, Xia; Engelhard, Mark H.; Matthews, Bethany E.; Zhong, Lirong; Wu, Haiping; Jia, Hao; Ren, Xiaodi; Gao, Peiyuan; Chen, Zonghai; et al.
Abstract: LiNi x Mn y Co1− x − y O2 (NMC) cathode materials with Ni ≥ 0.8 have attracted great interest for high energy‐density lithium‐ion batteries (LIBs) but their practical applications under high charge voltages (e.g., 4.4 V and above) still face significant challenges due to severe capacity fading by the unstable cathode/electrolyte interface. Here, an advanced electrolyte is developed that has a high oxidation potential over 4.9 V and enables NMC811‐based LIBs to achieve excellent cycling stability in 2.5–4.4 V at room temperature and 60 °C, good rate capabilities under fast charging and discharging up to 3C rate (1C = 2.8 mA cm −2 ), and superior low‐temperature discharge performance down to −30 °C with a capacity retention of 85.6% at C/5 rate. It is also demonstrated that the electrode/electrolyte interfaces, not the electrolyte conductivity and viscosity, govern the LIB performance. This work sheds light on a very promising strategy to develop new electrolytes for fast‐charging high‐energy LIBs in a wide‐temperature range. Abstract : Advanced localized high‐concentration electrolytes are developed to inhibit Ni dissolution and particle cracking in high‐Ni (≥0.8) LiNi x Mn y Co1− x − y O2 cathode materials when cycling under 4.4 V through formation of uniform, robust, and conductive electrode/electrolyte interfaces, thus enabling excellent long‐term cycling stability in a wide‐temperature range, superior fast‐charging and fast‐discharging capabilities, and superior low‐temperture performance when compared to conventional electrolytes.